What we forgot to bury - Montgomery, Marin (Thomas & Mercer, 2020)
Charlotte Coburn has a tragically dark past. But she's safe now. She lives in a gated community, protected from danger. When teenager Elle knocks at her door looking for shelter during a particularly severe storm, the woman can't help but think how lucky Elle's been to have found someone as friendly as her. Except Elle chose her door on purpose ... She knows all about Charlotte's secrets because they ruined her family and her life. And it is time that everyone else knew. But Charlotte's past has left a dark void in her life, so she is concocting her own vicious plan, convinced that Elle can help fill that void. As events unfold, the truth unravels and pulls both women into a dangerous game that will leave you wondering, Who's the villain?